The impact of primary care organization on avoidable hospital admissions for diabetes in 23 countries. (2nd January 2016) - Van Loenen, Tessa; Faber, Marjan J.; Westert, Gert P.; Van den Berg, Michael J.
Abstract: Objective : Diabetes is a so-called ambulatory care sensitive condition. It is assumed that by appropriate and timely primary care, hospital admissions for complications of such conditions can be avoided. This study examines whether differences between countries in diabetes-related hospitalization rates can be attributed to differences in the organization of primary care in these countries.Design : Data on characteristics of primary care systems were obtained from the QUALICOPC study that includes surveys held among general practitioners and their patients in 34 countries. Data on avoidable hospitalizations were obtained from the OECD Health Care Quality Indicator project. Negative binomial regressions were carried out to investigate the association between characteristics of primary care and diabetes-related hospitalizations.Setting : A total of 23 countries.Subjects : General practitioners and patients.Main outcome measures : Diabetes-related avoidable hospitalizations.Results : Continuity of care was associated with lower rates of diabetes-related hospitalization. Broader task profiles for general practitioners and more medical equipment in general practice were associated with higher rates of admissions for uncontrolled diabetes. Countries where patients perceive better access to care had higher rates of hospital admissions for long-term diabetes complications. There was no association between disease management programmes and rates of diabetes-related hospitalization. Hospital bed supply was strongly associated with admission rates for uncontrolled diabetes and long-term complications.Conclusions : Countries with elements of strong primary care do not necessarily have lower rates of diabetes-related hospitalizations. Hospital bed supply appeared to be a very important factor in this relationship. Apparently, it takes more than strong primary care to avoid hospitalizations. Key points: Countries with elements of strong primary care do not necessarily have lower rates of diabetes-related avoidable hospitalization. Hospital bed supply is strongly associated with admission rates for uncontrolled diabetes and long-term complications. Continuity of care was associated with lower rates of diabetes-related hospitalization. Better access to care, broader task profiles for general practitioners, and more medical equipment in general practice was associated with higher rates of admissions for diabetes.